Situações didáticas olímpicas para o ensino de funções: o contributo da engenharia didática de segunda geração - Lima, Francisco Daniel Souza de (2019)
Mathematical Olympiads currently play an important role in arousing curiosity about mathematical knowledge. However, despite the significant participation of students in the competitions, there is a great lack of didactic material more attractive and convergent with information technologies. Thus, the present work aims to offer a teaching methodology focused on the Theory of Educational Situations (TSD) and the Second Generation Teaching Engineering (EDSG) research methodology. First, we carried out a bibliographical survey of dissertations in the area of Mathematics Teaching, specifically those related to olympiads, aiming to map researches that might provide methodological subsidies beyond the conventional list of exercises. Once the need for methodologies that extend the approach to mathematics has been verified, we have concentrated our efforts on elaborating a series of Olympic Teaching Situations (SDO), supported by GeoGebra software, in order to contribute to the training of mathematics teachers in the approach to Olympic problems of OBMEP, specifically those related to the topic "functions", in the second phase of OBMEP in its three level.